ANALISIS PENGGUNAAN MEDIA NILAI TEMPAT BILANGAN DALAM PEMBELAJARAN MATEMATIKA KELAS II DI MI/SD - Deni Indrian, Novita; Nuryami; Fadilah, Yulina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of using place value media in teaching mathematics to second-grade students at Madrasah Ibtidaiyah (MI) or elementary schools (SD). The concept of place value—including units, tens, and hundreds—is a fundamental component in early mathematics education. However, many students struggle to grasp this concept abstractly. Therefore, concrete instructional media such as Dienes blocks, number cards, and place value charts are employed as visual aids to facilitate learning. This research uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the use of place value media significantly enhances students' understanding of number concepts. Students become more engaged, enthusiastic, and are better able to solve problems. These findings suggest that appropriate instructional media play a vital role in improving the quality of mathematics learning in lower primary education.